Optimalisasi Biaya Distribusi Produk dengan Menggunakan Vogel's Approximation Method di PT. LF Beauty Manufacturing - Elfitria Wiratmani; Ilham Falani; Siti Humayro Billah; Anton Oktavianto; Hoesup Pamoajer; Syaefudin Akbar (Universitas Indraprasta PGRI Jakarta, 2022)
The distribution of products from a company to consumers is very important. This greatly affects the level of consumer satisfaction, and will have a huge impact on the company. Problems often occur in product delivery where the costs incurred by the company are not optimal. The method used in this study is to implement Vogel's Approximation Method (VAM) with the aim of optimizing product distribution costs so as to produce minimum costs. Based on the results of this study, it was found that the distribution costs of the product were more optimal than the distribution costs of the previous company